Managing Green Innovation and Digital Transformation as an Approach to Building Entrepreneurial and Sustainable Educational Institutions An Applied Study on Libyan Public Universities: University Of Zawiya and Tripoli University as Case Studies (Al-Farooq Journal of Sciences, 2026)
In light of the rapid global transformations toward the green economy and the digital revolution, higher education institutions have become increasingly required to adopt modern strategies that integrate innovation, sustainability, and digital transformation in order to enhance institutional efficiency and achieve academic entrepreneurship. From this perspective, the present study aims to analyze the role of green innovation management in building entrepreneurial and sustainable educational institutions, while examining the mediating role of digital transformation in Libyan public universities through an applied study on University of Zawia and University of Tripoli.The study adopted the descriptive analytical approach and utilized a questionnaire as the primary data collection instrument. The questionnaire was distributed to a random sample of (200) faculty members and administrative staff from the two universities under investigation. The study focuses on measuring the level of green innovation management practices, the extent of digital transformation, and their impact on enhancing institutional sustainability and university entrepreneurship.Furthermore, the study seeks to identify the integrative relationship between modern environmental management and digital technologies, and their role in improving academic and administrative performance, as well as supporting Libyan universities’ orientation toward becoming smart and sustainable institutions capable of adapting to global changes. The significance of the study lies in its contribution to providing a contemporary theoretical and practical framework linking green innovation, digital transformation, and university sustainability, thereby supporting the development of educational and administrative policies in Libyan higher education institutions. The findings are expected to enhance institutional awareness of the importance of investing in green technologies and digital transformation to achieve sustainable excellence and competitiveness.
Keywords: Green Innovation Management, Digital Transformation, University Sustainability, Entrepreneurial Universities, Libyan Public Universities, University of Zawia, University of Tripoli